Em cena a história ensina : a produção de narrativas visuais na perspectiva da educação histórica - Prado, Alethéia Paula Lapas (2018)
As professionals responsible for the teaching of History, the search for new methods of teaching leading to the historical significant learning is essential in our days. We are facing a new generation of students to learn actively. We need to know the particulars, the ways of learning of these students, so that the historical knowledge makes sense. My goal, through this work, is to understand how the lessons of History, making use of your audiovisual dramatization and serving, can help young students to develop your historical consciousness and stimulate dialogue between historical imagination and science, from the investigation of narrative productions staged by the students of classes of the ninth year of a State school located in the municipality of Juara, Mato Grosso. The dramatization as didactic instrument consists of a practice that seeks to explore the creative potential of each student, as well as enhance oral expression and their subjectivities. For the teaching of History, the dramatization backed the use of discursive and argumentative resources that Chronicle human actions over time. By analyzing these productions narratives, it is possible to understand how our young students design the past and which senses attach to the story. As a work methodology, we intend to discuss the audiovisual language and use qualitative research techniques for analysis of the sources that are videos produced by students where stage Contemporary Conflicts related topics. In the perspective of historical education, an analysis of the narratives produced by young students is revealing. Through narratives, students demonstrate their cognitive elaborations and discursive resources. Knowing the relationship between the narrative and expression of historical consciousness, it is possible that teachers develop methodologies in that narrative is in evidence.